Entrepreneurial orientation : epistemological, theoretical, and empirical perspectives - Corbett, Andrew C.; Kreiser, Patrick M.; Marino, Louis D.; Wales, William J. (Advances in Entrepreneurship, Firm Emergence and Growth Ser., 2021)
In a world defined by increasing uncertainty and complexity, understanding the concept of Entrepreneurial Orientation (EO) is of critical importance. This volume convenes some of the world's leading experts on EO to provide readers with an overview of the current state of EO research and set a compelling agenda for its future.